IDEAL LIFE PHILOSOPHY REVEALED IN THE EPICS OF KALIDASA - Patel, Maheshkumar G.; Bariya, Pravinkumar Kalubhai (ShodhKosh: Journal of Visual and Performing Arts, 2021)
If seen from the main point of view, the world is materialistic. The success of life is to remain free from the shackles of the journey of life starting from childhood till death and to remain engaged in one's work like a lotus. Literature highlights the aspects related to life, literature has been created in various forms, in which the one starting from Vedas is called Vedic literature and from the worldly point of view it is worldly literature. In worldly literature, the epics written on the basis of Ramayana and Mahabharata are especially eye-catching. The art of living an ideal life seems to be developing on the basis of the portrayal of the characters depicted in this epic. The seeds of the art of living are found in a refined form in the Sanskrit epic. Knowledge of literary subjects stirs up the feelings within a person, which awakens the feeling of doing new work in his life and he becomes enlightened towards himself.